2014
DOI: 10.1111/pan.12564
|View full text |Cite
|
Sign up to set email alerts
|

Are new supraglottic airway devices, tracheal tubes and airway viewing devices cost‐effective?

Abstract: Over the past two decades, a plethora of new airway devices has become available to the pediatric anesthetist. While all have the laudable intention of improving patient care and some have proven clinical benefits, these devices are often costly and at times claims of an advantage over current equipment and techniques are marginal. Supraglottic airway devices are used in the majority of pediatric anesthetics delivered in the U.K., and airway-viewing devices provide an alternative for routine intubation as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 71 publications
1
2
0
Order By: Relevance
“…However, as Simon et al reported, the placement of a F-LMA can be more difficult when an appropriate technique is not used. 13 We also agree with this view, and we believe that this difficulty can be overcome by using an appropriate technique and with increasing experience.…”
Section: Discussionsupporting
confidence: 73%
“…However, as Simon et al reported, the placement of a F-LMA can be more difficult when an appropriate technique is not used. 13 We also agree with this view, and we believe that this difficulty can be overcome by using an appropriate technique and with increasing experience.…”
Section: Discussionsupporting
confidence: 73%
“…However, the first generation of cLMA is still widely used in clinical practice, especially in patients undergoing minor surgeries by providing a safe and effective alternative to tracheal intubation [3,4]. The standard recommended cLMA placement technique is performed blindly and requires full insertion of the index finger into the mouth [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Sir —We commend Slinn et al . for their recent article reviewing device cost‐effectiveness in pediatric airway management.…”
mentioning
confidence: 99%